Sharia Economic Perspective on The Improvement of Community Economy Through Joint Business Groups - Farida Isroani; Munir Munir; Eko Arief Cahyono (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
Indonesia is a country with the 4th largest population in the world. If the population size is large, if it is not followed by an increase in the quality of the population, it will certainly have an impact on poverty. Talking about the problem of poverty in Indonesia has decreased since 1976. There are two objectives of this study, the first is to determine the effect of economic growth on reducing poverty in Indonesia. And the second objective is to determine the effect of financial sector growth on poverty reduction in Indonesia. This study uses the VAR method with estimated data from 2000 to 2012. This reduction in poverty can occur as a result of economic growth and growth in the financial sector, which have increased every year. The results of this study indicate that economic growth has a negative and significant effect on poverty. The research also shows that the growth of the financial sector has an insignificant effect on poverty reduction.